Sistem Pengukur Berat Badan Dan Tinggi Badan Dengan Pencatatan Otomatis Berbasis Internet Of Things - Ilham, Ilham; Yulianto, Romi; Amiruddin, Amran; Iskandar, Akbar (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2022)
The weight and height measurement tools used at the Tarowang Jeneponto Health Center do not get accurate data, because they are still conventional or manual. this has an impact on inefficient use because it is still carried out by humans who have inaccuracies and usually human error occurs. This study aims to design an accurate and automatic body weight and height measurement system at the Tarowang Jeneponto Public Health Center. This data was obtained through field research, library research, interviews and documentation. The method used in this research is the blackbox method and UAT (User Acceptance Test). The results of this study indicate that the System for Measuring Weight and Height with Internet Of Things-Based Automatic Recording was successfully implemented and very well used with a questionnaire value of 86.4%.